2003
DOI: 10.1128/jcm.41.12.5384-5388.2003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Helicobacter pylori in Medium Supplemented with Cyanobacterial Extract

Abstract: Solid and liquid media supplemented only with a cyanobacterial extract (CE) and free of fetal calf serum (FCS), blood, and its derivatives support the growth of Helicobacter pylori. A total of 11 strains of H. pylori isolated from gastric biopsy samples were successfully subcultured in Mueller-Hinton agar supplemented with 0.4% CE. When this medium was used for primary isolation of H. pylori, a low isolation rate (30%) was observed because of the abundant growth of contaminants. The growth kinetics of eight is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Under the permanent process of swallowing microbiota inhabiting the oral cavity or food derived microbial DNA are characterized as well. In studies on cultivable bacterial microbiota of the human stomach, samples are spread to conventional media (Vega et al, 2003 ) without adapting the culture conditions to those present in the natural gastric habitat (Sanduleanu et al, 2001 ; Delgado et al, 2013 ; Khosravi et al, 2014 ). We suggest that gastric habitat like conditions would be inevitable for serious conclusions on viability and above all proliferation capability of isolated microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Under the permanent process of swallowing microbiota inhabiting the oral cavity or food derived microbial DNA are characterized as well. In studies on cultivable bacterial microbiota of the human stomach, samples are spread to conventional media (Vega et al, 2003 ) without adapting the culture conditions to those present in the natural gastric habitat (Sanduleanu et al, 2001 ; Delgado et al, 2013 ; Khosravi et al, 2014 ). We suggest that gastric habitat like conditions would be inevitable for serious conclusions on viability and above all proliferation capability of isolated microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…This low frequency might be due to the limitation of the IFA or caused by the unusually long generation time of slowly growing H. pylori cells, as previously reported (37). We also determined the generation time (t g ) of H. pylori cells from the linear segment of the growth curve (log 2 OD 600 values plotted against time [see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vega et al. [9] studied media supplemented with cyanobacterial extract and showed that growth rates with this supplement are at least as good and partly even significantly better than with fetal calf serum (FCS). This media supplement is considerably more cost‐efficient than FCS, easier to manufacture and store and also provides for enhanced compliance with the requirement for reducing the use of animal products.…”
Section: Culturementioning
confidence: 99%